Idiopathic toe-walking in childhood - S. A. Malmberg (Русский журнал детской неврологии)
Background. Idiopathic toe walking (ITW) in childhood is a benign age-dependent disorder of the normal walking formula.Objective: neurological, catamnestic and electromyographic analysis of patients with ITW.Materials and methods. The study group consisted of 59 patients aged 1 year 4 months to 15 years (mean age is 6.10 ± 3.54 years) with a predominance of males (76 %) and the onset of violations in the age of 4 years in 83 % of cases, a normal history and the absence of signs of organic neurological deficiency.Results and conclusions. As a result of differential diagnosis cerebral palsy, spastic paraplegia, peripheral neuropathy, myopathy and other diseases as possible causes of ITW were excluded. A high proportion of comorbid disorders of the neurotic spectrum in patients with ITW was determined, so tranquilizing and anxiolytic therapy was indicated in half of the patients. Electromyography doesn’t revealed pathology of peripheral neuromotor apparatus. Follow-up monitoring for 2–6 years, showed complete spontaneous regression of violations of the pattern of the walk at 84.8 % of the patients of 7–8 years of life. The formation of contractures of the ankle joint in 5 patients required operative correction. The issues of therapeutic tactics (gypsuming, orthosis of feet, botulinum toxin therapy, physiotherapy) were discussed. The absence of evidence-based effect of therapeutic measures is confirmed.